CLASSIFYING VIDEO GAME TRANSLATION STUDIES FROM TRANSTEXTUALITY PERSPECTIVES - SF. Lukfianka Sanjaya Purnama; SF. Luthfie Arguby Purnomo (UIN Raden Mas Said Surakarta, 2019)
This paper attempts to classify video game translation(VGT)studies from the perspectives of transtextuality, Genette’s term referring to the relationships a text weaves with other texts (1992). In regard to VGT studies, applying transtextuality signifies the textuality of video game and its transtextual relationship with other texts. Transtextuality is linear to the connectionist perspectives Globalization, Internationalization, Localization, and Translation (GILT) holds, a conventional concept that houses VGT, emphasizing on the intra and inter relationships between the four elements of GILT. This necessity to consider VGT as a part of GILT is the linearity to which transtextuality conforms VGT studies. Applying transtexuality, VGT studies are classified into transversality, transcreation, transfiguration, and transmediation. Transversalityreferstothestudiesaimed at applying translation theories in VGT.Transcreation refers to VGT studies that focus on cultural issues in relation to video game mechanics. Transfiguration refers to VGT studies that incorporate game studies as a response to certain VGT issues. Transmediation refers to VGT studies that focus on the influence of video game media toward the translation aspects of video games. These four classifications construct a quadrant which opens probabilities for VGT studies to depart from the combination of each element.